Pengaruh Kualitas Produk, Citra Merek dan Persepsi Harga Terhadap Minat Beli Susu Bear Brand - Putri Permata Sari; Maria Septiantini Alie (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the simultaneous and partial influence of product quality, brand image and price perception on interest in buying bear brand milk among the people of Kutoarjo Village. The research methodology used is a quantitative approach with data collection methods using questionnaires. The population in this study was the people of Kutoarjo Village and the sample determined using probability sampling using proportional sampling obtained 317 respondents for people who had never bought Bear brand milk. Then the data was obtained using multiple linear analysis. The results of the research show that product quality (X1), brand image (X2), price perception (X3) partially have a positive and significant effect on interest in buying bear brand milk. Simultaneously product quality, brand image and price perception influence interest in buying bear brand milk. amounting to 33.8%.